Evaluation of high purity cellulose production from pretreated various agricultural biomass wastes. (March 2019) - Maryana, R; Jatmiko, T H; Prasetyo, D J; Rizal, W A; Suwanto, A; Praharasti, A S; Indrianingsih, A W; Anwar, M; Rizaluddin, A T
Abstract: Four kinds of non-wood biomass were studied as raw material for high purity cellulose production. Cajuput ( Melaleuca Leucadendron ) twigs, sugarcane ( Saccharum officinarum ) bagasse, oil palm ( Elaeis guineensis ) empty fruit bunch and rice ( Oryza sativa ) straw were treated by NaOH 1 % at boiling temperature and atmospheric pressure for 2 h. The surface structure of these materials and chemical modification of cellulose, hemicellulose, and lignin during the treatment were analyzed. The result showed that the highest cellulose increasing was from 29.6 to 62.7% for rice straw. Meanwhile, the highest and the lowest cellulose content after treatment were 69.7% for sugarcane bagasse and 48.0% for cajuput, respectively. Scanning electron microscopy (SEM) image showed that the smoother surface for all biomass after pre-treatment.